Orthodontic bracket bonding techniques and adhesion failures - Almoabady, Ebraheem Hamed; Alkahtani, Reem Mohammed; Alotaibi, Noura Fahad; Alsuli, Mona Abdulmohsen; Alonazi, Amera Saud; Alanazi, Badriah Ayed; Madani, Sara Ahmed; Ghadeer, Sara Abdulaziz Bin; Alabbad, Hawraa Mohammad; Wahbi, Lulwa Ali Al; Alqahtani, Mohammed Abdullah (International Journal Of Community Medicine And Public Health, 2024)
The introduction of glass ionomer cements in orthodontics aimed to address the drawbacks of the acid-etch technique using composite resins, including demineralization, enamel damage, and potential allergic reactions. These cements release fluoride over time, potentially protecting against demineralization. Glass ionomer cements, despite their benefits in reducing adhesive residue and protecting against demineralization, showed higher bond failure rates compared to composite resins. This is attributed to their sensitivity to application techniques and moisture, along with a delayed setting time. In contrast, light-cured composite resins, preferred over chemically-cured resins in recent years, offer advantages such as ease of use, consistent handling, and controlled setting. However, early trials indicated higher bond failure rates for light-cured resins, a finding not consistently replicated in later studies. While glass ionomer cements offer certain advantages, their higher bond failure rate poses a significant limitation. Light-cured composite resins, with their user-friendly characteristics, have become the preferred choice in orthodontic bonding despite initial concerns about higher bond failure rates.